2017
DOI: 10.1002/lary.26480
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and speech perception in noise difficulties in Fanconi anemia

Abstract: 4. Laryngoscope, 127:2358-2361, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Jos e Vale reported that about 50% of patients with FA had hearing impairments. Verheij et al [4] reported that 55.2% of the patients enrolled in their study had hearing impairments. Other studies indicate that only 11% of patients with FA had hearing impairments [1,2].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Jos e Vale reported that about 50% of patients with FA had hearing impairments. Verheij et al [4] reported that 55.2% of the patients enrolled in their study had hearing impairments. Other studies indicate that only 11% of patients with FA had hearing impairments [1,2].…”
Section: Discussionmentioning
confidence: 90%
“…Early diagnosis helps to avoid disabilities and to improve speech and language development. Consequently, patients with Fanconi anemia should undergo pure-tone audiograms and speech tests as early as possible [4]. The Fanconi Anemia Guidelines for Diagnosis and Management recommend that all children with FA should undergo follow-up examinations with an otolaryngologist and audiologist for a comprehensive ear examination and audiologic evaluation, even if they had undergone standard newborn hearing screening tests [5].…”
Section: Introductionmentioning
confidence: 99%
“…As it appears to be the rule in FA, the structural abnormality range is wide. The following alterations have been described: small tympanic membrane in 62%, malformed malleus in 33-57%, bony islands at tympanic membrane in 48%, pinna malformations (including microtia) in 10-35%, abnormal course or prominence of the chorda tympani nerve in 34%, narrow external auditory canal in 32%, narrow internal auditory canal in 6%, and atresia of the external auditory canal in 3% ( 177 , 178 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 99%
“…This translates into mild and moderate degrees of hearing impairment ( 177 180 ), particularly decreased hearing has been associated with the presence of structural ear anomalies ( 3 ). Assessment through the speech perception in noise test showed that up to 53% of evaluated patients had hearing impairment ( 178 ).…”
Section: Dysmorphological and Oncological Phenotype Of Patients With ...mentioning
confidence: 99%